Development of Augmented Reality-Based Interactive Multimedia to Improve Critical Thinking Skills in Science Learning - Syawaludin, Ahmad; Gunarhadi, Gunarhadi; Rintayati, Peduk (International Journal of Instruction, 2019)
This study aimed to describe the development of augmented reality-based interactive multimedia to improve the critical thinking skills of elementary school teacher education students in learning earth structure and fisheries material science. This type of research was research and development by Sukmadinata consisting of preliminary studies, model development, and model testing. The research subjects were elementary school teacher education students at Sebelas Maret University, Indonesia. The technique of collecting data used tests, questionnaires, and observations. The collected data was then analyzed qualitatively and quantitatively. Qualitative data analysis used the interactive models of Miles and Huberman and quantitative data analysis using a paired sample t-test. The results of the study show that the development of media products determines indicators of learning, programming, display, and curriculum. The main field test obtained ?value = 0.002< 0.05, it can be decided that H0 rejected. Students think critically using augmented reality-based interactive multimedia better than before using it. At present, it is obtained interactive multimedia based on augmented reality that is feasible to use in accordance with the views of experts and users.